Identification of good candidates for valgus bracing as a treatment for medial knee osteoarthritis. Issue 1 (21st August 2017) - Clouthier, Allison L.; Hassan, Elizabeth A.; Brandon, Scott C. E.; Campbell, Aaron; Rainbow, Michael J.; Deluzio, Kevin J.
ABSTRACT: Valgus unloader braces are a conservative treatment option for medial compartment knee osteoarthritis that aim to unload the damaged medial compartment through application of an external abduction moment. Patient response to bracing is highly variable, however. While some experience improvements in pain, function, and joint loading, others receive little to no benefit. The objective of this work was to analyze clinical measures and biomechanical characteristics of unbraced walking to identify variables that are associated with the mechanical effectiveness of valgus unloader bracing. Seventeen patients with medial knee osteoarthritis walked overground with and without a valgus unloader brace. A musculoskeletal model was used to estimate the contact forces in the medial compartment of the tibiofemoral joint and brace effectiveness was defined as the decrease in peak medial contact force between unbraced and braced conditions. Stepwise linear regression was used to identify clinical and biomechanical measures that predicted brace effectiveness. The final regression model explained 77% of the variance in brace effectiveness using two variables. Bracing was more effective for those with greater peak external hip adduction moments and for those with higher Kellgren–Lawrence grades, indicating more severe radiographic osteoarthritis. The hip adduction moment was the best predictor of brace effectiveness and was well correlated with several other measures indicating that it may be functioning as a "biomarker" for good bracing candidates. Clinical Significance: The ability to predict good candidates for valgus bracing may improve issues of patient compliance and could enable the ability to train patients to respond better to bracing. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:351–356, 2018.